Grey wolf optimization for combined heat and power dispatch with cogeneration systems. (January 2016) - Jayakumar, N.; Subramanian, S.; Ganesan, S.; Elanchezhian, E.B.
Graphical abstract: GWO to CHPD. Highlights: Grey wolf optimizer is used to solve combined heat and power economic dispatch. Practical aspects such as valve-point effects, emission, transmission loss, spinning reserve, and ramp rate are considered. In the proposed approach the total fuel cost and emissions are simultaneously minimized. Dynamic economic dispatch has been carried out. Results are compared to those published in the recent state-of-the art literatures. Abstract: The Combined Heat and Power Dispatch (CHPD) is an important optimization task in power system operation for allocating generation and heat outputs to the committed units. This paper presents a Grey Wolf Optimization (GWO) algorithm for CHPD problems. The effectiveness of the proposed method is validated by carrying out extensive tests on three different CHPD problems such as static economic dispatch, environmental-economic dispatch and dynamic economic dispatch. Valve-point effects, ramp-rate limits and spinning reserve constraint along with network loss are considered. Standard test systems containing 4, 7, 11 and 24 units are used for demonstration purpose. To validate the performance of the GWO, statistical measures like best, mean, worst, standard deviation, epsilon, iter and sol-iter over 50 independent runs are taken. The simulation experiments reveal that GWO performs better in terms of solution quality and consistency.